Structuring effective copreneurial teams - S. M. Farrington; E. Venter; C. Eybers; C. Boshoff (South African Journal of Business Management, 2011)
Despite growing numbers and increased research attention, few empirical studies have focused on copreneurial family businesses, and hardly any guidelines exist on how these couples should manage their marriage and business relationships. Against this background the primary objective of this study was to empirically assess the influence of selected structural-based factors on the effectiveness of South African copreneurships. The teamwork literature proposes that the success of a team depends on how the team is structured or set up, but the empirical findings of this study demonstrate that elements of structure are related to certain measures of success but not to others. More specifically, the results suggest that the success of a marriage between copreneurs is not influenced by the success of the business, but that the more structural elements such as Leadership, Needs alignment and Role clarity are in place, the more satisfied the spouses are likely to be with both their business and their marital relationship.
Keywords: 650